Intervention AUVs: The next challenge. (2015) - Ridao, Pere; Carreras, Marc; Ribas, David; Sanz, Pedro J.; Oliver, Gabriel
Abstract: While commercially available AUVs are routinely used in survey missions, a new set of applications exist which clearly demand intervention capabilities. The maintenance of permanent underwater observatories, submerged oil wells, cabled sensor networks, pipes and the deployment and recovery of benthic stations are a few of them. These tasks are addressed nowadays using manned submersibles or work-class ROVs, equipped with teleoperated arms under human supervision. Although researchers have recently opened the door to future I-AUVs, a long path is still necessary to achieve autonomous underwater interventions. This paper reviews the evolution timeline in autonomous underwater intervention systems. Milestone projects in the state of the art are reviewed, highlighting their principal contributions to the field. To the best of the authors' knowledge, only three vehicles have demonstrated some autonomous intervention capabilities so far: ALIVE, SAUVIM and GIRONA 500, being the last one the lightest one. In this paper GIRONA 500 I-AUV is presented and its software architecture discussed. Recent results in different scenarios are reported: (1) valve turning and connector plugging/unplugging while docked to a subsea panel, (2) free floating valve turning using learning by demonstration, and (3) multipurpose free-floating object recovery. The paper ends discussing the lessons learned so far.